PENYUNTINGAN NASKAH TERJEMAHAN SAMARKAND KARYA ANONIM - Gita Aulia Utami (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2023)
The objectives of this research are as follows: (1) to explain the process of editing translated manuscripts; (2) to describe the difficulties/challenges in editing translated manuscripts; and (3) to provide solutions in addressing the existing difficulties/challenges. This research employs a qualitative approach using descriptive analysis method. This means that the researcher edits the manuscripts, describes the process, identifies the arising issues, and provides alternative solutions. The analyzed stages of mechanical editing include translation and editing of words, phrases, and sentences. This classification is done because there are still many errors found in translating words, phrases, and sentences. The difficulties faced by translators, which also pose challenges for the researcher as an editor, are as follows: (1) ambiguity of the meaning of words, phrases, and sentences; (2) difficulty in finding equivalent words, phrases, and sentences; (3) inadequate familiarity with cultural words in the source text; (4) influence of the form and type of words, phrases, and sentences in the source language; and (5) influence of the source language. These difficulties can be overcome by: (a) referring to the source text and comparing it with the translated manuscript to be edited; (b) employing editing techniques specific to translated manuscripts; (c) mastering the theme and having knowledge of the translated manuscript; (d) consulting directly with the translator; and (e) if possible, consulting with the original author of the manuscript as well.